(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
The purchasing decision is the process by which consumers decide to buy a product or service. To enhance the purchasing decision, there are factors that influence it, such as digital marketing and excellent service. Digital marketing is one form of effort to promote a company or goods or services in order to build a reference in marketing its products by utilizing technology. Excellent service is the best maximum effort provided to meet the needs according to the desires of service users. The purpose of this research is to determine the effect of digital marketing and excellent service on purchasing decisions both partially and simultaneously. The research was conducted at PT. Deroyal Tour & Travel. The population of the study is infinite, with a sample size of 90 people. The sample was determined using the purposive sampling technique. Data collection was done through interviews, documentation, and questionnaires measured using a Likert scale. The analysis technique used was multiple linear regression. The results show that digital marketing has a positive and significant effect on purchasing decisions, excellent service has a positive and significant effect on purchasing decisions, and the independent variables simultaneously have a positive and significant effect on the dependent variable. The recommendation given is to improve service and adjust promotions through social media to increase purchasing decisions at PT. Deroyal Tour & Travel."